Motor vehicle incidents in postgraduate trainees in British Columbia - Cassidy, Louise; Croft, Emma; Erdelyi, Shannon; Brubacher, Jeffrey (Canadian Medical Education Journal, 2021)
Introduction: Postgraduate medical trainees frequently work ≥ 24- hour shifts causing fatigue and adverse consequences such as motor vehicle incidents (MVIs). We aim to determine the incidence of MVIs during the commutes of trainees in British Columbia (BC) in the preceding year. Methods: We completed a retrospective, cross-sectional survey of trainees regarding work hours, shifts, and MVIs in the previous year. MVIs included falling asleep while driving, sudden braking or swerving to avoid a collision, unintentionally running a red light or stop sign, or collisions. Results: Of 273 respondents, over half (54.6%) reported ≥1 MVI, one in 14 were in a collision (7.0%), and two thirds (66.3%) reported that the safety of their commute had been impacted by fatigue in the past year. After adjustment for road exposure and shift-related factors, every ten km increase in commute length was associated with an increased risk of MVI (aOR=1.54;95%CI:1.15-2.12). Reported attentional failures, such as unintentionally running a red light and/or stop sign, increased for every ten hours on-call (aOR=1.44;95%CI:1.03-2.04) and for every additional past-midnight shift worked (aOR=1.13;95%CI:1.01-1.26). Discussion: Trainees with longer and more frequent commutes had an increased risk of MVIs. Trainees who worked more hours on-call and more past-midnight shifts reported significantly more attentional failures while commuting. This study helps us understand factors affecting trainee commuter safety and supports calls for the provision of safe alternatives to commuting for postgraduate trainees.